CMC foliations of open spacetimes asymptotic to open Robertson-Walker spacetimes - Gerhardt, Claus (Pure and applied mathematics quarterly, 2021)
We consider open globally hyperbolic spacetimes N of dimension n + 1, n >= 3, which are spatially asymptotic to a Robertson-Walker spacetime or an open Friedmann universe with spatial curvature (k) over tilde = 0,-1 and prove, under reasonable assumptions, that there exists a unique foliation by spacelike hypersurfaces of constant mean curvature and that the mean curvature function tau is a smooth time function if N is smooth. Moreover, among the Friedmann universes which satisfy the necessary conditions are those that reflect the present assumptions of the development of the universe.
Gesehen am 04.03.2022